2003
DOI: 10.1111/j.1365-2621.2003.tb07064.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Reticulum Ca2+‐ATPase and Cytochrome Oxidase as Indicators of Frozen Storage in Cod (Gadus morhua)

Abstract: Activities of 2 membrane-bound enzymes, Ca 2+ -ATPase from the sarcoplasmic reticulum and cytochrome oxidase from the inner mitochondria membrane, were measured during frozen storage of cod. Enzyme activities were higher in cod muscle samples frozen at -30 °C than at -20 °C. Freezing-induced activation of both enzymes was observed and the activation was amplified by ice storage prior to freezing. Sensory evaluation conducted at 9 mo of frozen storage showed differences between the sensory properties of cod fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This is in agreement with the results of Godiksen et al (2003), who were able to distinguish between cod stored for 5 months at −30 (highest SR Ca 2+ -ATPase activity) and −20 • C. Hsu et al (1993) reported a more rapid decrease in actomyosin Ca 2+ -ATPase activity in Pacific Whiting stored at −8 • C compared to samples stored at −20, −34, and −50 • C. However, del did not observe any significant differences between actomyosin Ca 2+ -ATPase activity in hake fillets stored at −20 and −30 • C for 49 weeks. The activity decreased significantly at both temperatures, and no activity was detected from 36 weeks onward, which was ascribed to denaturation of actomyosin.…”
Section: Ca 2+ -Atpase Activitysupporting
confidence: 95%
See 1 more Smart Citation
“…This is in agreement with the results of Godiksen et al (2003), who were able to distinguish between cod stored for 5 months at −30 (highest SR Ca 2+ -ATPase activity) and −20 • C. Hsu et al (1993) reported a more rapid decrease in actomyosin Ca 2+ -ATPase activity in Pacific Whiting stored at −8 • C compared to samples stored at −20, −34, and −50 • C. However, del did not observe any significant differences between actomyosin Ca 2+ -ATPase activity in hake fillets stored at −20 and −30 • C for 49 weeks. The activity decreased significantly at both temperatures, and no activity was detected from 36 weeks onward, which was ascribed to denaturation of actomyosin.…”
Section: Ca 2+ -Atpase Activitysupporting
confidence: 95%
“…Inoue et al (1992) reported an increased Ca 2+ -ATPase activity of frozen carp myosin during the first 12 h of frozen storage for samples stored at −15 and −20 • C, while the activity of samples stored at −5 to −13 • C decreased. Activation of SR Ca 2+ -ATPase activity as a result of freezing was also reported by Godiksen et al (2003), who suggested that the freeze-induced activation of the enzyme was due to changed interactions between Ca 2+ -ATPase and the surrounding membrane lipids.…”
Section: Ca 2+ -Atpase Activitymentioning
confidence: 63%
“…Myosin accounts for 50% of myofibrillar protein, which is the main protein of muscle from aquatic animals, while the globular heads of myosin are responsible for the activity of Ca 2+ ‐ATPase, a membrane‐bound enzyme (Godiksen et al . 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This result indicated that superchilling could mitigate the decrease of Ca 2+ -ATPase activity in grass carp. Myosin accounts for 50% of myofibrillar protein, which is the main protein of muscle from aquatic animals, while the globular heads of myosin are responsible for the activity of Ca 2+ -ATPase, a membrane-bound enzyme (Godiksen et al 2003). Ca 2+ -ATPase is greatly inactivated by protein denaturation, especially in the head region (Benjakul et al 2003;Zhou et al 2006).…”
Section: Ca 2+ -Atpase Activitymentioning
confidence: 99%
“…The active site of Ca 2+ -ATPase is in the globular head of myosin [29]. Thus, the Ca 2+ -ATPase activity is a good indicator of the integrity of actomyosin molecule and protein freeze denaturation.…”
Section: Actomyosin Ca 2+ -Atpase Activitymentioning
confidence: 99%